The effectiveness of breastfeeding self-efficacy intervention on implementation of breastfeeding in low-birth-weight infants: a systematic review - Utami, Resti; Arief, Yuni Sufyanti (Journal of the Pakistan Medical Association, 2023)
Objective: To present an overview of breastfeeding self-efficacy interventions to enhance the implementation of exclusive breastfeeding for mothers with low birth weight infants. Method: The systematic review comprised search for randomised controlled trials and quasi-experimental studies published between January 2014 to January 2022 on Scopus, ScienceDirect, Sage journals, ProQuest, Google Scholar and PubMed databases using the Population-Intervention-Comparison-Outcome framework and in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses checklist. The analytical quality of the studies was assessed using the Critical Appraisal Skills Programme checklist. Results: Of the 339 studies initially identified, 10(2.94%) qualified for detailed analysis. Breastfeeding self-efficacy interventions could notably enhance the implementation of exclusive breastfeeding. Conclusion: Breastfeeding self-efficacy interventions can be modified and effectively used by nurses to improve the implementation of exclusive breastfeeding for mothers with low birth weight infants. Keywords: Breastfeeding, Milk, Infant, Low birth weight, Intervention.